Pyrolysis of C-60-thin films yields Ni-filled sharp nanotubes - Grobert, N; Terrones, M; Osborne, A; Terrones, H; Hsu, W; Trasobares, S; Zhu, Y; Hare, J; Kroto, H; Walton, D (1998)
Highly graphitised needle-like elongated carbon nanostructures containing encapsulated Ni, are produced by heating alternating thin films of C-60 and Ni on a silica plate at 950 degrees C. High Resolution Transmission Electron Microscopy (HRTEM) studies reveal that these tapering structures are fully filled with Ni and are closed at both ends. The diameters of the needles (ca. 2-5 mu m in length) range between 10-20 nm at one end and 30-200 nm at the other. A surprisingly high degree of graphitisation was observed for the nanostructures. They may prove to be useful as Scanning Tunnelling Microscope (STM) tips due to their shape.